KONSELING INDIVIDU BERBASIS VIRTUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MASA PANDEMI COVID-19 - Muhammad Rizal Januri; Aziz Muslim (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
The ability of students to learn cannot be separated from the influence of motivation, both internally and externally, especially when the learning system is carried out online, so that it does not rule out the possibility of an impact on a decrease in students' learning motivation, so as a counseling guidance teacher has an important role in increasing students’ learning motivation. The purpose of this study is to increase student learning motivation through virtual during the COVID-19 at SMK Negeri 5 Yogyakarta. This study uses a qualitative method with a descriptive type, which describes the results of research from sources through written words. Data collection techniques were carried out through document studies and interviews. Data analysis uses the form of analysis from Miles and Huberman in the form of data reduction, presentation, and drawing conclusions. In the implementation of individual counseling there are several stages carried out by guidance and counseling teachers in increasing student motivation, including; stage of problem identification, prognosis, diagnosis, evaluation and follow-up. On the other hand, there are four principles that are used as a reference by guidance and counseling teachers in implementing counseling services, namely the level of responsiveness to counselee problems, providing understanding related to the importance of learning motivation, directions on how to determine planning and interests related to learning motivation, and strengthening system support. After these stages are carried out according to the procedures in counseling services, the results of the study show that virtual can increase student learning motivation.